2018
DOI: 10.1017/s0373463318000978
|View full text |Cite
|
Sign up to set email alerts
|

A Revisit of the Definition of the Ship Domain based on AIS Analysis

Abstract: When ships approach each other, they should keep a minimum area around them clear of other vessels in order to remain safe. The geometrical shape of this area has been studied since the early 1970s and is defined as the ship domain. The progress in computer capacity since then and the introduction of the Automatic Identification System (AIS) provides the potential to further investigate the size and the governing factors of the domain. This investigation revisits and proposes a method using data based on 600,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 18 publications
(34 reference statements)
2
30
0
Order By: Relevance
“…In the literature, many ship domains with various shapes and scales have been proposed in previous studies, including ellipse domain, circle domain and polygon domain. It should be pointed out that ship domain sizes are related to ship length in the majority of previous studies but Hörteborn et al (2019) found that the ship domain is not affected by ship length. Fujii and Tanaka (1971) assumed the ship domain is an ellipse in their study of traffic capacity estimation in Japanese waters.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In the literature, many ship domains with various shapes and scales have been proposed in previous studies, including ellipse domain, circle domain and polygon domain. It should be pointed out that ship domain sizes are related to ship length in the majority of previous studies but Hörteborn et al (2019) found that the ship domain is not affected by ship length. Fujii and Tanaka (1971) assumed the ship domain is an ellipse in their study of traffic capacity estimation in Japanese waters.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Since in Subsection 2.1 the waterway was divided into several lanes, which has already taken the lateral safe distance into account, this section only deals with the longitudinal safe distance between ships in the same lane. Most of the research results show that the longitudinal size of the ship domain is roughly proportional to the length of the ship (Liu et al, 2011; Qi et al, 2011; Hansen et al, 2013; Liu et al, 2016; Hörteborn et al, 2019; Zhou and Zheng, 2019). As mentioned above, the length of a ship can be denoted by ; then, based on the ship domain, the safe distance between a ship and its preceding ship in the same lane can be calculated by Equation (2): where is the multiple of safe distance relative to ship length.…”
Section: Methodsmentioning
confidence: 99%
“…Pietrzykowski also employed the method of collecting ship domain knowledge to obtain training samples, trained the fuzzy neural network model, and determined the ship domain model in a narrow channel and open water area (Pietrzykowski, 2008; Pietrzykowski and Uriasz, 2009). Based on 600,000 ship encounters in 36 locations, Hörteborn analysed the determination of the ship domain model boundary scale and discussed the factors that influence the scale (Hörteborn et al, 2018).…”
Section: Related Workmentioning
confidence: 99%